2020
DOI: 10.1002/ecs2.3213
|View full text |Cite
|
Sign up to set email alerts
|

Management of remnant tallgrass prairie by grazing or fire: effects on plant communities and soil properties

Abstract: Tallgrass prairie is a disturbance‐dependent ecosystem that has suffered steep declines in the midwestern United States. The necessity of disturbance, typically fire or grazing, presents challenges to managers who must apply them on increasingly small and fragmented parcels. The goal of this study was to compare effects of management using cattle grazing or fire on vegetation and soil characteristics to aid managers in making decisions regarding the kind of disturbance to apply. We selected 73 sites, of which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
24
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(29 citation statements)
references
References 58 publications
4
24
1
Order By: Relevance
“…However, most remnants experienced either minimal change or reductions in soil bulk density, which facilitated soil kg C and N m −2 loss and could be due to land management. In a study of over 70 remnant tallgrass prairies, Larson et al [66] found that grazing increased soil bulk density more than other management types, and it is possible that remnant prairie at Midewin remains affected by the soil compaction caused by grazers present up until 1997. However, Larson et al [66] reported average bulk densities of approximately 1.0 g cm −3 for grazed remnants and 0.8 g cm −3 for burned, which are consistent with our results where the bulk density at Midewin's remnants are also lower (Figure 2).…”
Section: Response Variablementioning
confidence: 99%
See 1 more Smart Citation
“…However, most remnants experienced either minimal change or reductions in soil bulk density, which facilitated soil kg C and N m −2 loss and could be due to land management. In a study of over 70 remnant tallgrass prairies, Larson et al [66] found that grazing increased soil bulk density more than other management types, and it is possible that remnant prairie at Midewin remains affected by the soil compaction caused by grazers present up until 1997. However, Larson et al [66] reported average bulk densities of approximately 1.0 g cm −3 for grazed remnants and 0.8 g cm −3 for burned, which are consistent with our results where the bulk density at Midewin's remnants are also lower (Figure 2).…”
Section: Response Variablementioning
confidence: 99%
“…In a study of over 70 remnant tallgrass prairies, Larson et al [66] found that grazing increased soil bulk density more than other management types, and it is possible that remnant prairie at Midewin remains affected by the soil compaction caused by grazers present up until 1997. However, Larson et al [66] reported average bulk densities of approximately 1.0 g cm −3 for grazed remnants and 0.8 g cm −3 for burned, which are consistent with our results where the bulk density at Midewin's remnants are also lower (Figure 2). Removal of grazing and periodic prescribed burning in remnants decreases soil compaction and promotes organic matter accumulation, which both facilitate decreases in soil bulk density, but soil factors such as drainage that are variable between Midewin remnants play important roles in the rate at which SOM accumulates.…”
Section: Response Variablementioning
confidence: 99%
“…Another critical management approach at Nachusa has been regular prescribed fire, and the average fire return interval is less than 2 years. Regular fire is critical to maintaining levels of plant species richness and coefficient of conservatism (Larson et al, 2020), and has consistently been identified as necessary to maintain intact tallgrass prairie habitat (Alstad et al, 2016;Bowles & Jones, 2013;Ratajczak, Nippert, Briggs, & Blair, 2014). Regular prescribed fire is likely the primary driver in sustaining the rare native plant communities in Nachusa native prairies.…”
Section: Native Prairiesmentioning
confidence: 99%
“…Follett et al's [3] study of grazing practices indicted that long-term, moderate grazing can improve soil health and stabilize sandy soil. Larson et al [22] compared the outcomes of grazing and prescribed fire, and reported that grazing increased soil bulk density and total soil nitrogen while recent fire did not alter any soil properties but increased species richness. Teague et al [15] compared the restoration outcomes of grazing prescriptions (light continuous season-long grazing, heavy continuous grazing, and multi-paddock grazing) on ungrazed prairie, and found that multi-paddock grazing is better for biodiversity conservation than continuous season-long grazing.…”
Section: Introductionmentioning
confidence: 99%
“…Despite these studies comparing the outcomes of grazing versus prescribed fire, and grazing of varying duration and intensity, it is still a challenge for native prairie managers to decide what practices to apply [22]. This is because the outcomes of native prairie management remain difficult to predict and contain significant uncertainties [8,23].…”
Section: Introductionmentioning
confidence: 99%